Single-session nutritionist-led counseling improves health self-efficacy among teachers - Sholihah, Lini Anisfatus; Dini, Cleonara Yanuar; Gusrianto, Wildan Alfira; Aulia, Salma Shafrina (Alma Ata University Press, 2025)
Background: The increasing prevalence of obesity and metabolic syndrome (MetS) among teachers necessitates targeted interventions to enhance health outcomes. Nutritionist-led counseling can enhance health self-efficacy by equipping individuals with knowledge, skill, and confidence to have healthier lifestyles. Objective: The study aims to assess whether a single face-to-face counseling intervention can significantly improve self-efficacy among teachers.Methods: This experimental study employed a pre-and-post-test design involving 23 high-school vocational teachers (14 females and 9 males) who participated in a one-day, three-hour counseling session by trained nutritionists. Participants underwent anthropometric measurements and MetS risk screening before the intervention. Self-efficacy was assessed using a validated questionnaire before and after counseling. Statistical analyses were conducted using paired t-tests and chi-square or Fisher's Exact tests.Results: The findings indicated a significant increase in self-efficacy scores from a baseline mean of 26±2 to 28±2 after the intervention (p<0.001). Notably, the proportion of teachers who reported confidence in selecting appropriate foods significantly improved (p=0.02). The prevalence of obesity among participants was high, with 57% categorized as obese based on BMI.Conclusion: Targeted nutrition counseling can effectively enhance self-efficacy among teachers, potentially leading to healthier lifestyle confidence and reduced MetS risk. This study underscores the importance of incorporating nutritionist-led interventions in educational settings to promote health among teachers, who serve as role models for students.